PENERAPAN PROGRAM SATU MURID SATU POHON LITERASI DENGAN BERBANTUAN LITERACY CLOUD UNTUK MENINGKATKAN MINAT BACA MURID KELAS VIC SD NEGERI 22 DAUH PURI - I MADE SUBA (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
The COVID-19 pandemic has brought major changes in various sectors. One of them is in the field of education which requires implementing distance learning. The impact of distance learning on the school literacy movement by reading 15 minutes before learning cannot be carried out optimally. Based on the results of initial observations, students' interest in reading and writing is low. So that teachers need to innovate learning in the implementation of the school literacy movement. The researcher innovated the application of the one student one literacy tree program with the help of the Literacy Cloud. This program aims to increase the interest in reading and writing of class VIC SD Negeri 22 Dauh Puri students. Because reading can open new horizons and world horizons and can foster a positive culture and national character values ??so that a golden generation is born with the profile of Pancasila students. Based on the results and data analysis of this study, it showed an increase in student interest in reading from the initial data in February of 42.11%. After implementing the One Student One Literacy Tree program with the help of literacy cloud so that in March it became 50.66%, in April 2022 it increased to 71.38% in the medium category and in May 2022 it increased to 81.74% in the high category. Thus the One Student One Literacy Tree program with the help of the Literacy Cloud can significantly increase the reading and writing interest of class VIC SD Negeri 22 Dauh Puri students. ABSTRAKPandemi covid-19 membawa perubahan besar di berbagai sektor. Salah satunya adalah di bidang pendidikan yang mengharuskan melaksanakan pembelajaran jarak jauh. Dampak pembelajaran jarak jauh gerakan literasi sekolah membaca 15 menit sebelum belajar tidak dapat terlaksana secara maksimal. Berdasarkan hasil obervasi awal minat baca dan tulis murid rendah. Sehingga guru perlu melakukan inovasi pembelajaran dalam pelaksanaan gerakan literasi sekolah. Peneliti melakukan inovasi penerapan program satu murid satu pohon literasi dengan berbantuan Literacy Cloud. Program ini bertujuan untuk meningkatkan minat baca dan tulis murid kelas VIC SD Negeri 22 Dauh Puri. Karena membaca dapat membuka wawasan baru dan cakrawala dunia serta dapat menumbuhkan budaya positif dan nilai-nilai karakter bangsa sehingga lahir generasi emas yang berkarakter profil pelajar Pancasila. Berdasarkan hasil dan analisis data penelitian ini menunjukkan adanya peningkatan minat baca murid dari data awal pada bulan Pebruari sebesar 42,11%. Setelah dilaksanakan program Satu murid satu pohon literasi berbantuan literacy cloud sehingga pada Maret menjadi 50,66%, pada bulan April 2022 meningkat dengan capaian 71,38% dengan kategori sedang dan bulan Mei 2022 meningkat menjadi 81,74% dengan kategori tinggi. Dengan demikian program Satu Murid Satu Pohon Literasi dengan berbantuan Literacy Cloud dapat meningkatkan minat baca dan tulis murid kelas VIC SD Negeri 22 Dauh Puri secara signifikan.